2022
DOI: 10.1186/s13020-022-00579-7
|View full text |Cite
|
Sign up to set email alerts
|

Revealing potential anti-fibrotic mechanism of Ganxianfang formula based on RNA sequence

Abstract: Background Ganxianfang (GXF) formula as a traditional Chinese medicine (TCM) is used for liver fibrosis in clinical practice while its mechanism is unclear. The aim of this study is to explore the molecular mechanism of GXF against CCl4-induced liver fibrosis rats. Methods Detected the main compounds of GXF by UPLC-MS/MS. Evaluated the efficacy of GXF (1.58, 3.15, 4.73 g/kg/day) and Fuzheng Huayu (FZHY, positive control, 0.47 g/kg/day) through seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Evidence demonstrated that certain pathways play a role in developing organ fibrosis. For example, RNA-seq and single-cell sequencing were performed on rat liver tissues with CCl4-induced fibrosis, suggesting that fibrosis is closely related to the Chemokine signaling pathway ( Liu et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence demonstrated that certain pathways play a role in developing organ fibrosis. For example, RNA-seq and single-cell sequencing were performed on rat liver tissues with CCl4-induced fibrosis, suggesting that fibrosis is closely related to the Chemokine signaling pathway ( Liu et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…Euryale ferox seed (EFS) is a typical representative of "a medicine food homology species", as described in the Huangdi Nei Jing Tai Su (黄帝内经太素): "Eating it as food on an empty stomach, and taking it as medicine for patients" [1,2]. EFS is the dried seeds of the E. ferox Salisb.…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of gut microbiota could be an important target for QSW [ 12 ] to produce neuroprotective effects but also for Hua-Feng-Dan to produce neuroprotective effects [ 17 ] fortifying the role of metal composition and herbal interactions in herbo-mineral preparations. RNA-Seq technology was also employed to analyze the adaptive mechanism of hepatoprotection with cinnabar and realgar-containing Hua-Feng-Dan [ 18 ] and antihepatic fibrotic mechanism with Ganxianfang formula [ 19 ].…”
mentioning
confidence: 99%